2017
DOI: 10.1186/s12893-017-0226-x
|View full text |Cite
|
Sign up to set email alerts
|

Delayed gastric emptying following pancreatoduodenectomy with alimentary reconstruction according to Roux-en-Y or Billroth-II

Abstract: BackgroundDelayed gastric emptying (DGE) remains the most frequent complication following pancreatoduodenectomy (PD) with published incidences as high as 61%. The present study investigates the impact of bowel reconstruction techniques on DGE following classic PD (Whipple-Kausch procedure) with pancreatogastrostomy (PG).MethodsWe included 168 consecutive patients who underwent PD with PG with either Billroth II type (BII, n = 78) or Roux-en-Y type reconstruction (ReY, n = 90) between 2004 and 2015. Excluded we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
21
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 28 publications
(25 citation statements)
references
References 49 publications
3
21
0
1
Order By: Relevance
“…Das Auftreten von Erbrechen und die Anwendung prokinetischer Substanzen war in beiden Gruppen gleich verteilt. Trat eine MES auf, so verlängerten sich sowohl die Dauer des Intensivaufenthaltes (3 [1-4,75] vs. 2 [1][2][3] Tage, p = 0,007) als auch die Dauer des Gesamtkrankenhausaufenthaltes (22 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]75] vs. 18 [14][15][16][17][18][19][20][21][22] Tage, p = 0,001) signifikant. Ein präoperativ vorbestehender Diabetes mellitus war ein Risikofaktor für eine MES (p = 0,047), außerdem zeigten sich weniger MES, wenn Somatostatinanaloga (SA) verabreicht wurden (MES55 % ohne SA, 36 % mit SA, p = 0,034).…”
Section: Ergebnisseunclassified
“…Das Auftreten von Erbrechen und die Anwendung prokinetischer Substanzen war in beiden Gruppen gleich verteilt. Trat eine MES auf, so verlängerten sich sowohl die Dauer des Intensivaufenthaltes (3 [1-4,75] vs. 2 [1][2][3] Tage, p = 0,007) als auch die Dauer des Gesamtkrankenhausaufenthaltes (22 [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32]75] vs. 18 [14][15][16][17][18][19][20][21][22] Tage, p = 0,001) signifikant. Ein präoperativ vorbestehender Diabetes mellitus war ein Risikofaktor für eine MES (p = 0,047), außerdem zeigten sich weniger MES, wenn Somatostatinanaloga (SA) verabreicht wurden (MES55 % ohne SA, 36 % mit SA, p = 0,034).…”
Section: Ergebnisseunclassified
“…8 Other factors include disruption of vagal innervation, pylorospasm as a consequence of pyloric devascularization after pyloric-preserving pancreaticoduodenectomy (PPPD), 9 the extent of gastrectomy, 10 or the methods of reconstruction for alimentary tract. 11,12 In addition, intra-abdominal abscess, peripancreatic collections or pancreatic fistula were speculated to be the predisposing factors of secondary DGE. 13 Consequently, multiple efforts have been advocated to prevent DGE after PD.…”
Section: Introductionmentioning
confidence: 99%
“…Decreased plasma motilin level after resection of the gastric antrum and duodenum is believed to contribute to DGE because within these structures exist high levels of motilin secretion endocrine cells 8 . Other factors include disruption of vagal innervation, pylorospasm as a consequence of pyloric devascularization after pyloric‐preserving pancreaticoduodenectomy (PPPD), 9 the extent of gastrectomy, 10 or the methods of reconstruction for alimentary tract 11,12 . In addition, intra‐abdominal abscess, peripancreatic collections or pancreatic fistula were speculated to be the predisposing factors of secondary DGE 13 …”
Section: Introductionmentioning
confidence: 99%
“…Effective treatments for early recovery of oral dietary intake are lacking, resulting in prolonged hospital stay and interval before the induction of adjuvant therapy. 1,2 The incidence of DGE after PD varies from 4.5% to 100% across studies, 3,4 implying difficulties in defining diagnostic criteria and incomplete understanding of its pathophysiology. We previously traced oral dietary intake after PD in detail to clarify the impact on the diagnosis of DGE and short-term postoperative outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…In general, surgical procedures influenced DGE, indicating the superiority of pylorus resection, 7 antecolic gastrojejunostomy or duodenojejunostomy reconstruction, 8 Braun anastomosis, 9 Billroth II reconstruction 10,11 and side-to-side gastrojejunostomy. 12,13 However, recent studies including a meta-analysis reported conflicting findings, [2][3][4][14][15][16] resulting in a lack of evidencebased effective procedures that decrease DGE consistently. Few studies have focused on pharmacological treatment for DGE after PD.…”
Section: Introductionmentioning
confidence: 99%